Occupant- Centric Simulation- Aided Building Design Theory, Application, and Case Studies - O'Brien, William; Tahmasebi, Farhang (Taylor & Francis, 2023)
Occupant-Centric Simulation-Aided Building Design promotes occupants as a focal point for the design process. This resource for established and emerging building designers and researchers provides theoretical and practical means to restore occupants and their needs to the heart of the design process. Helmed by leaders of the International Energy Agency Annex 79, this edited volume features contributions from a multi-disciplinary, globally recognized team of scholars and practitioners. Chapters on the indoor environment and human factors introduce the principles of occupant-centric design while chapters on selecting and applying models provide a thorough grounding in simulation-aided building design practice. A final chapter assembling detailed case studies puts the lessons of the preceding chapters into real-world context. In fulfillment of the International Energy Agency's mission of disseminating research on secure and sustainable energy to all, Occupant-Centric Simulation-Aided Building Design is available as an Open Access Gold title. With a balance of fundamentals and design process guidelines, Occupant-Centric Simulation-Aided Building Design reorients the building design community toward buildings that recognize and serve diverse occupant needs, while aiming for superior environmental performance, based on the latest science and methods.